Implementation of the Danish return-to-work program: process evaluation of a trial in 21 Danish municipalities - Birgit Aust; Maj Britt D Nielsen; Gry Grundtvig; Helle L Buchardt; Linnea Ferm; Irene Andersen; Trine L Lund; Martin Ohmann Claudio Jelle; Malene F Andersen; Jørgen V Hansen; Torill Tverborgvik; Trine Helverskov; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: The aim of this study was to evaluate the implementation of the Danish national return-to-work (RTW) program in 21 Danish municipalities. METHODS: We conducted a structured process evaluation on (i) reach and recruitment, (ii) fidelity, (iii) dose-delivered, (iv) dose-received, and (v) context by formulating 29 implementation criteria and analyzing qualitative and quantitative data from administrative records, interviews, field notes, and questionnaires. RESULTS: All municipalities integrated the basic features of the RTW program into the existing framework of the sickness benefit management system to an acceptable degree, ie, establishment of RTW teams, participation of RTW team members in the training courses, and following the general procedures of the program. However, the level of implementation varied considerably between the municipalities, particularly with respect to fidelity (defined as implementation consistent with the principles of the interdisciplinary RTW process). Five municipalities had high and eight had low fidelity scores. Similar large differences were found with regard to dose-delivered, particularly in the quality of cooperation with beneficiaries, employers, and general practitioners. Only 50% of the first consultations with the RTW coordinator were conducted in time. Among participants who were employed when their sickness absence period started, only 9% had at least one meeting with their workplace. CONCLUSION: It was feasible to implement the basic features of the Danish RTW program, however, large variations existed between municipalities. Establishment of well-functioning interdisciplinary RTW teams might require more time and resources, while ensuring early assessment and more frequent cooperation with employers might need more general adjustments in the Danish sickness benefit system.